Lichen Nitidus Presenting with Nail Changes—Case Report and Review of the Literature. Issue 3 (2nd December 2014) - Tay, Evelyn Yuxin; Ho, Madeline Sheun Ling; Chandran, Nisha Suyien; Lee, Joyce Siong‐See; Heng, Yee Kiat
Abstract Lichen nitidus of the nail is rare and can precede the onset of skin lesions. Delayed diagnosis is common. We present an unusual case of lichen nitidus–associated nail changes that preceded the onset of skin lesions in a 4‐year‐old Indian girl. We also conduct a review of six other cases of lichen nitidus with nail involvement from the English‐language literature. Clues to the diagnosis of lichen nitidus include violaceous or pigmentary changes of the nail fold and subtle lichenoid papules on the affected digits. Lichen nitidus of the nails appears to be less severe than nail changes of lichen planus and is generally self‐limiting. Understanding the natural history of lichen nitidus of the nails will help physicians better counsel patients and their families.